Private Politics and Peasant Mobilization Mining in Peru - Gustafsson, Maria-Therese (Development, Justice and Citizenship, 2018)
"In this insightful book on relationships between multinational mining companies and local communities, Maria-Therese Gustafsson shines new light on local struggles to deepen democracy and redefine the terms of international corporate investment in the Peruvian Andes." -Kenneth Roberts, Cornell University, USA "This book is a must-read for academics and students, as well as potential investors in natural resources, governmental officials and activists that seek to avoid not only the irruption of conflicts, but also the ongoing destruction of communities in Latin America and other resource-rich regions." -Benedicte Bull, University of Oslo, Norway "By comparing two cases of resistance to the expansion of mining in Peru, the author convincingly points at the relations between communities' organizational strengths, big corporations' governance strategies and state institutions' interventions." -Donatella della Porta, Scuola Normale Superiore di Pisa, Italy This book explores how different corporate governance strategies affect community mobilization and the scope for influence when an area's population is faced with the arrival of the extraction industry. Drawing on ethnographic research into Peruvian mining localities, the author analyses a series of relationships which are characterized by confrontations, clientelism, demobilization and strategic collaboration. By presenting a detailed account of micro practices and showing how these processes are interpreted by different groups, Gustafsson offers a refined understanding of the multiple layers and informal workings of power between transnational corporations and local communities.